Class (Non)Voting in Switzerland 1971‐2011: Ruptures and Continuities in a Changing Political Landscape. Issue 4 (9th September 2014) - Rennwald, Line
Abstract1 This article deals with the evolution of class voting in Switzerland from 1971 to 2011. It shows that class cleavage (working class versus owners/employers) has weakened in Switzerland. The existence of a large right‐wing party with strong support among the working class contributes to blurring the traditional class divisions in voting. However, the analysis indicates that class cleavage has not completely disappeared. The centre‐right parties display much continuity in their class basis over time, thus contributing to the persistence of class cleavage. Besides taking into account the diversity of the right‐wing parties, the article also offers a new perspective by including nonvoting. Class differences in turnout are important in Switzerland, but the findings suggest that the most important change over time concerns party choice and not turnout.